OPTIMASI PRODUKSI ENZIM AMILASE DARI BAKTERI LAUT JAKARTA (ARTHROBACTER ARILAITENSIS) Â - Purnawan, A.; Capriyanti, Y.; Kurniatin, PA.; Rahmani, N.; ., Yopi (JURNAL BIOLOGI INDONESIA, 2015)
ABSTRACTAmylase is one of the most important industrial enzymes which can be used in a number of industrial processes including food industry, textile, paper industry, renewable energy, and pharmaceutical. This study reports the environmental conditions and nutrient media for amylase production from marine bacterium Arthrobacter arilaitensis. Various parameters such as substrate concentration, pH medium, temperature of fermentation, co-substrate, and nitrogen source was determined to obtain the optimum conditions. Maximum amylase enzyme production was obtained at starch concentration 1%, pH 7, temperature fermentation 30°C, co-substrate maltose with activity 2.7 U/mL. While the addition of several nitrogen sources was given decreased amylase activity, such as addition casein was decreased the activity into 2.3 U/mL. Keywords: Arthrobacter arilaitensis, amylase activity, optimization, co-substrate, pH, temperature, substrate, nitrogen source